PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHINGUNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI - Rubinem ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The problem in this research is the low results of students' mathematics learning class II SD Negeri 010 Silikuan Hulu, from 34 students only 10 students or 29.41% were resolved. Based on this the researchers conducted a classroom action research with the aim of improving learning outcomes through the application of mathematical models of quantum teaching learning. This study was conducted by two cycles, each cycle consisting of two meetings and one daily tests, the instrument used is the observation sheet activities of teachers and students and math achievement test. The data collection technique used is the technique of observation and tests of learning outcomes. The study states that penarapan quantum model of teaching can enhance the activity of teachers and students and mathematics learning outcomes second grade students SD Negeri 010 Silikuan Hulu. This is supported by: (a) the activities of teachers in each cycle increases, in the first meeting of the first cycle of activities for teachers to get a score of 35, or 67.3% to the category quite well, at the first meeting the first cycle of activities for teachers to get a score of 41 or 78.8 % good category. At the first meeting of the second cycle increased with the acquisition of a score of 44 or 82.6% with very good categories and the second meeting of the second cycle obtain a score of 50 or 96.1% with very good category. Activities of students has increased, at the first meeting the first cycle of activity students obtain a score of 28 or 58.3% to the category quite well, at the first meeting the first cycle of activity students obtain a score of 34 or 70.8% in both categories. At the first meeting of the second cycle increased with the acquisition of a score of 43 or 89.5% with very good categories and the second meeting of the second cycle obtain a score of 46 or 95.8% to the category of very good; and (b) the results of students in each cycle has increased, the base score is the number of students who pass the 21 students with a percentage of 61.7% with the acquisition of an average value of 60.7. In the first cycle has increased the number of students who pass are 26 students with a percentage of 76.4% with the acquisition of an average value of 83.3. In the second cycle the number of students who pass the increase in the number of 34 students with a percentage of 88.23% with an average value of 92.7.